2002
DOI: 10.1046/j.1432-1033.2002.03031.x
|View full text |Cite
|
Sign up to set email alerts
|

Ruk is ubiquitinated but not degraded by the proteasome

Abstract: The regulator of ubiquitous kinase (Ruk) protein, also known as CIN85 or SETA, is an adaptor‐type protein belonging to the CD2AP/CMS family. It was found in complexes with many signaling proteins, including phosphoinositol (PtdIns) 3‐kinase (EC 2.7.1.137), Cbl, GRB2, p130Cas and Crk. Functional analysis of these interactions, implicated Ruk in the regulation of apoptosis, receptor endocytosis and cytoskeletal rearrangements. We have recently demonstrated that overexpression of Ruk induces apoptotic death in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…3). While it has previously been demonstrated that the coiled-coil domain of SETA can mediate multimerization Verdier et al, 2002) this is the first instance to our knowledge, of a SETA-binding partner showing a preference for SETA dimers.…”
Section: Discussionmentioning
confidence: 62%
“…3). While it has previously been demonstrated that the coiled-coil domain of SETA can mediate multimerization Verdier et al, 2002) this is the first instance to our knowledge, of a SETA-binding partner showing a preference for SETA dimers.…”
Section: Discussionmentioning
confidence: 62%
“…However, neither IP of SETA and antiubiquitin Western blot, nor cotransfection of an HA-tagged polyubiquitin provided evidence that SETA itself is polyubiquitinated (data not shown). We did not investigate the monoubiquitination of SETA, because it has been established that the protein is modified in this way (32,37).…”
Section: Seta Can Modulate the Polyubiquitination Of Egfr By Cblsmentioning
confidence: 99%
“…Of these proteins, epsin, Eps15, ␤-arrestin, and CIN85 are known to be ubiquitinated. Specifically, they are modified with monoubiquitin (4,7,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The Cbl ubiquitin ligase was recently found to recruit a complex of CIN85 with another endocytic protein, endophilin, to facilitate the internalization of activated, ubiquitinated growth factor receptors (5,23). Furthermore, CIN85 is monoubiquitinated at an unknown site(s) by both Nedd4 and Cbl (7,18).…”
mentioning
confidence: 99%